Sense of coherence promotion and occupational and family stress mitigation may improve heart health behaviors in middle-aged working women: a structural equation modelling approach - Moon, Ji Hyun; Seo, Eunhye (Frontiers in Public Health, 2024)
Aims: This study aimed to construct a model that describes heart health behaviors in middle-aged working women and verify the goodness-of-fit of the model based on Salutogenesis. Methods and Results: This study adopted a cross-sectional design. Participants were 330 middle-aged working women in South Korea. Data were analyzed using structural equation modelling with Sobel's Z test.In the multiple mediation model, stress coping strategy (β = .26; p < .001), social support (β = .41; p < .001), and health self-efficacy (β = .36; p < .001) had significant direct effects on sense of coherence (SOC). SOC had a significant direct effect on occupational (β = -.72; p < .001) and family stress (β = -.76; p < .001). Additionally, SOC (β = .67; p < .001), occupational stress (β = -.46; p < .001), and family stress (β = -.28; p < .001) had significant direct effects on heart health behaviors. Moreover, SOC had a significantly partial mediating effect on heart health behaviors through occupational stress (Z = 3.17; p = .002) and family stress (Z = 2.26; p = .024). Conclusions: Occupational and family stress mediated the relationship between SOC and heart health behaviors in middle-aged working women. Clinical Evidence: Interventions that mitigate occupational and family stress may improve heart health behaviors among middle-aged working women.